Development of high performance and efficient coating repair systems for offshore tropical marine environment - Agostinho, Francisco José (Centre for Materials Engineering, 2018)
Rehabilitation coatings of offshore equipment rarely perform as well as the original coating, despite the high cost involved. The performance gap is probably due to high relative humidity, salt contamination and limitations on the use of abrasive blast cleaning. Thus, this research aims to deepen the understanding of surface preparation parameters that affect organic coating performance. Carbon steel samples were subjected to a variety of surface alterations consisting of salt contamination, mechanical (wire brushing) and chemical (rust converter and remover) surface preparations followed by coating application and performance testing. The samples were first pre-corroded in a corrosion chamber to mimic degradation from service then surface preparations were performed after which a coating was applied. Coated new samples (RN) and fully corroded samples (SN) were the reference sets, while other samples were prepared to a variety of surface conditions. Visual inspection and electrochemical impedance spectroscopy (EIS) were performed prior to exposure and periodically during accelerated cycling corrosion testing for a period of 30 days. The visual condition of the samples was used to rank the performance of the prepared samples. These results were used as benchmark to decide the optimum EIS method, either phase angle at high frequency or total impedance at low frequency, for early evaluation of the organic coating performance under the conditions studied. Furthermore, adhesion pull-off testing was performed to rank the effectiveness of the coating over various prepared coating. The reference new samples (RN) proved to be the best surface condition and the corroded samples without preparation (SN) had the worst performance for all tests performed. In addition, it was established that salt contamination had a stronger impact on the coating performance than the amount of corrosion product remaining on the surface. Moreover, it was determined that the best preparation approach after precorrosion of the plates was to apply rust converter to the surface before coating. Adhesion measurement was of secondary concern on the studied coated surfaces as cohesive failure occurred on the pre-treatment layers rather than coating adhesion failure between the coating and the treated surface.